2016
DOI: 10.2306/scienceasia1513-1874.2016.42.259
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of ethyl acetate extract of Eclipta prostrata against 6-hydroxydopamine-induced neurotoxicity in SH-SY5Y cells

Abstract: ABSTRACT:Oxidative stress plays an important role in the pathogenesis of Parkinson's disease. The neurotoxin 6-hydroxydopamine initiates cellular oxidative stress which has been implicated in neurodegenerative conditions related to Parkinson's disease. Eclipta prostrata, also known as false daisy, is a plant belonging to the sunflower family. It is a rich source of phenolic compounds that confer the plant an antioxidant activity. In this study, we investigated the protective effects of ethyl acetate extract of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 22 publications
(23 reference statements)
0
10
0
Order By: Relevance
“…In recent years, much attention has been paid to the development of effective approaches in scientific communities for the prevention and treatment of lethal neurodegenerative diseases such as Parkinson’s disease, , Alzheimer’s disease, stroke, etc. Considering its relative pharmacological safety and efficacy, curcumin has been thought to be a representative of active drugs used for the prevention and treatment of neurodegenerative diseases, though the underlying mechanisms are not clearly understood.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, much attention has been paid to the development of effective approaches in scientific communities for the prevention and treatment of lethal neurodegenerative diseases such as Parkinson’s disease, , Alzheimer’s disease, stroke, etc. Considering its relative pharmacological safety and efficacy, curcumin has been thought to be a representative of active drugs used for the prevention and treatment of neurodegenerative diseases, though the underlying mechanisms are not clearly understood.…”
Section: Introductionmentioning
confidence: 99%
“…[50][51][52][53] It has been reported that once 6-OHDA penetrates and accumulates inside the neuron, it causes auto-oxidation nonenzymatically that impaired neuronal redox homeostasis, which ultimately leads to the enhanced formation of a variety of ROS which includes hydroxyl radicals, hydrogen peroxide, superoxide radical and quinones. [54][55][56] All these free radical species are responsible for causing mitochondria dysfunction with impaired electron transport chain and causes complexes I and IV malfunction, causing cellular depletion in ATP formation. [57,58] Thus, it can be concluded that OS-induced mitochondrial dysfunction was solely responsible for causing neurodegeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Ethyl acetate extract of E. prostrata suppressed the Bax/Bcl-2 ratio and reduced the activity of caspase-3, a key modulator of cell apoptosis. Ethyl acetate extract of E. prostrata has antioxidant capacity and attenuates SH-SY5Y cell death by blocking 6-hydroxydopamine-induced apoptotic signaling [7].…”
Section: Treat To Neurodegenerationmentioning
confidence: 99%
“…Gani and Devi [2] reported that E. prostrata has activity as antioxidant, antiviral, antifungal, antibacterial, and antihepatotoxic. E. prostrata can be used as a potential herb to prevent stress-induced oxidative neurodegeneration in Parkinson's disease [7]. The E. prostrata has pharmacological anti-myotoxic, antihemorrhagic, antiproliferative, antioxidant, antitumor, antihyperglycemic, antidementia, antimicrobial, antihyperlipidemic, antivenom, anti-HIV, and larvicidal activities [5].…”
Section: Introductionmentioning
confidence: 99%